Reappraising the multiple functions of traditional agriculture within the context of building rural development investigative skills (2014)
The productivist and reductionist vision of industrial agriculture in the twentieth century prevented the analysis of the other multiple functions of traditional agriculture, such as those corresponding to the ecological and cultural dimensions. In the current rural crisis, which entails food insecurity, environmental uncertainties, deterioration of the social fabric, a context lacking rural educational (extension) proposals and impaired quality of life, to name a few, it is necessary to reassess traditional agriculture in order to generate strategies that are capable of providing strategic answers to the problems in question. The current multifunctional agriculture (MFA) paradigm allows agricultural research in different world regions, addressing comprehensive economic aspects, protection of commons, actor-centered focus and public policy formulation. This article presents the current modern research contributions that, in the framework of the project: Rural Societies, Economy and Natural Resources integrating rural development skills, (Sociedades Rurales Economia y Recursos Naturales integrando competencias para el desarrollo rural - SERI DAR , which is part of the Alpha III program of the European Commission) and reveals and reappraises other functions of traditional agriculture that warrant investigation. In this way, the Universidad Nacional de Colombia contributes to the development of appropriate research skills by integrating post-graduate students in transdisciplinary research with local knowledge networks. We hypothesized that farmer adaptations contain practical and technical strategic guidance for the protection of common goods (soil, biodiversity, water, etc.) and the strengthening of the social fabric (knowledge and culture). With the reappraisal of the multiple functions of traditional agriculture and their upgrading in the context of post-industrial cultures, it is possible to build strategies that are capable of responding to the uncertainties produced by the global markets of food, land and technology, the reductionist knowledge systems and the environment.